An Assessment of Mangrove Rehabilitation Programs in Bolaang Mongondow Selatan Regency, North Sulawesi - Rignolda Djamaluddin (Sam Ratulangi University, 2020)
While the results of many mangrove rehabilitation efforts have not been optimal due to various factors, the rate of mangrove forest deforestation remains high in Indonesia. This research was designed to test the principle â€œplanting certain mangrove seedlings on suitable habitat would be survivedâ€. The test was based on an assessment of six locations in Bolaang Mongondow Selatan Regency where mangrove rehabilitation programs were implemented. This assessment was conducted by using a spot check method to analyze any variables associated with plantation area feasibility, and the use of a participative approach to collect additional information. Results from this study confirmed that mangrove seedlings have to be planted on the right habitat and that the implemented rehabilitation programs have followed a try and error or speculative approach, and have not been supported by sufficient technical and theoretical competencies.Â Keywords: artificial plantation, natural regeneration, mangrove, rehabilitationÂ Â Â Â Â Â Â Deforestasi hutan mangrove di Indonesia berlangsung cepat, sementara itu banyak upaya rehabilitasi belum memberikan hasil yang optimal karena berbagai faktor. Penelitian ini menguji secara khusus prinsip â€œbenih yang ditanam di tempat yang cocok akan tumbuhâ€, melalui penilaian enam lokasi program rehabilitasi mangrove di Kabupaten Bolaang Mongondow Selatan. Penilaian dilakukan menggunakan metode pengecekan lapangan (on spot check) untuk menganalisis variabel-variabel yang berkaitan dengan kelayakan lahan tanam, dan pengumpulan informasi melalui pendekatan partisipatif. Hasil penelitian menegaskan bahwa â€œjenis bibit yang ditanam harus sesuai dengan lahan tanamâ€. Upaya penanaman yang dilakukan masih menggunakan pendekatan coba-coba atau spekulatif, dan tidak didukung pemahaman teknis maupun teoritis yang memadai.Kata kunci: mangrove, penanaman artifisial, regenerasi alami, rehabilitasi